Asia-wide impacts of COVID-19 on national food systems and recovery paths - Piñeiro, Valeria; Laborde Debucquet, David (International Food Policy Research Institute, 2022)
2020 was marked by a global recession. Most Asian economies witnessed a major eco nomic downturn or, at the minimum, major decelerations in economic growth of magnitudes not seen since the 1997 Asian Financial Crisis. Being a major hub of globalization, Asia has suffered from both local supply disruptions caused by the COVID-19 restrictions and its policy responses and fallout in demand associated with the collapse on global markets. Economic recovery during 2021 was uneven. Expectations were that recovery during 2021 would promote economic activity back to the levels of 2019 in South Asia and East Asia,in Southeast Asia, though, the revival was expected to be delicate for a full recovery. Not all perturbations seen in 2020 and 2021 were COVID-19 related. Three countries in Asia faced country-specific crisis. Conflict was a major factor in Afghanistan and Myanmar, while North Korea did not suffer any registered COVID cases, and its woes were internal. This report assesses the impacts of the COVID-recession and recovery on household vul nerability, using a model-based analysis that captures the observed global macroeconomic trajectory as reported in the IMF’s World Economy Outlook of October 2021. By capturing observed growth patterns, the scenario analysis thus incorporates the economic conse quences of the supply disruptions captured and caused by the public health crisis as well as the effects of economic and social policy responses, such as fiscal stimulus and en hanced social protection. However, we do not include the household-level effects of tar geted safety nets, especially in 2020 and 2021.